Autistic Spectrum Disorder: causes, implications and perspectives for school inclusion (Research, Society and Development, 2023)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder of the affected individual, which can present three levels of severity: mild, medium, and severe. The real causes of autism are still unknown. However, its origin is related to chromosomal alterations in more than one chromosome of the human karyotype. This article sought to verify the perception of public school teachers regarding the proposed theme and the pedagogical strategies for the reception and inclusion of individuals affected by such pathology. Municipal and state education secretaries, as well as principals, secretaries and teachers from municipal and state schools in Bom Jesus - Piauí were interviewed using pre-structured questionnaires. It was verified that the education secretaries reported that the departments (Education Departments) have been promoting actions for the educational inclusion of students with Autism Spectrum Disorder (ASD) and other Special Education Needs (SENs), through the use of multifunctional resource rooms, rooms equipped with games, illustrated alphabet and handouts, in addition to partnerships established with Psychosocial Care Centers (CAPS) and care of these students in after-school hours. On the other hand, some principals reported that they do not receive any material for the inclusion of students with SENs, and that although some of the teachers stated that they had already taken training courses, most of the interviewees still do not feel unprepared to work with individuals with ASD.